Mpox clade I outbreak: how should Asia prepare and respond? - Lim, Poh Lian (2024)
The World Health Organisation (WHO) announced on 14 August 2024 that mpox is again a Public Health Emergency of International Concern (PHEIC). In the first PHEIC, declared in July 2022 and ended in May 2023, over 87,000 cases and 140 deaths across 111 countries were reported. The first global outbreak involved clade II mpox, which is endemic in West Africa and generally carries a lower case fatality rate. Transmission in that global outbreak was predominantly through sexual transmission among gay, bisexual and other men who have sex with men. The 2022–2023 PHEIC eventually ended through a combination of public health measures, including enhanced case detection, risk communications and vaccination.